In Silico Methods for Development of Generic Drug-Device Combination Orally Inhaled Drug Products - Ross L. Walenga; Andrew H. Babiskin; Liang Zhao (Wiley, 2019)
The development of generic, single‐entity, drug-device combination products for orally inhaled drug products is challenging in part because of the complex nature of device design characteristics and the difficulties associated with establishing bioequivalence for a locally acting drug product delivered to the site of action in the lung. This review examines in silico models that may be used to support the development of generic orally inhaled drug products and how model credibility may be assessed.